Selected Social Issues of the Lao People’s Democratic Republic - Ługowska, Oliwia; Szulc, Adam; Tarała, Sebastian (International Studies. Interdisciplinary Political and Cultural Journal, 2023)
As an object of Western public and media interest, Laos still appears to be an overlooked and unnoticed country. In a sense, it remains in the shadow of its larger neighbours Vietnam and Thailand, who capture the world’s attention in the context of the Indochina region, and the Lao People’s Democratic Republic itself remains rather on the sidelines of world politics. This state of affairs also relates to Western observers’ recognition of the social problems facing the country. I focus this article on providing an insight into the specific characteristics of Laos and defining the social problems the country has had to face over the past three decades. It answers questions about the characteristics of Laos, how it fares in the HDI ranking and what social challenges it faces. The thesis put forward by the authors is that the LRLD, as a moderately developed and ethnically diverse country, is confronted with the resulting social problems. The authors used the monographic method to conduct their research, which they based on an analysis of collected scientific publications, statistical data and internet sources. The research succeeded in confirming the hypothesis. The social problems plaguing the Lao People’s Democratic Republic have their origins primarily in the poor material situation of the majority of the population, the lack of infrastructure and the ethnic diversity that the authorities in Vientiane are unable to cope with. However, looking at the general trend of development in Laos, the scale and incidence of the issues described in the paper should gradually decrease.